Cover Feature: 17O NMR Studies of Yeast Ubiquitin in Aqueous Solution and in the Solid State (5/2021). (15th February 2021) - Lin, Binyang; Hung, Ivan; Gan, Zhehong; Chien, Po‐Hisu; Spencer, Holly L.; Smith, Steven P.; Wu, Gang
Abstract : Last piece of the puzzle in biomolecular NMR spectroscopy : The central theme of the design is the four "jigsaw puzzle pieces", which signify the fact that our 17 O NMR work represents the "last piece of the puzzle" in the field of biomolecular NMR. On the left is shown the ribbon structure of the protein studied in this work. On the right hand side is the design drawing of a series‐connected hybrid (SCH) 35.2‐T magnet (the most powerful NMR magnet in the world) on which we recorded the first set of 17 O NMR spectra for proteins. More information can be found in the communication by Z. Gan, S. P. Smith, G. Wu, et al.